Beyond Borders: Shedding Light on Foreign Bribery through an Islamic Legal Lens - Sauni, Herawan; Fernando, Zico Junius; Putra, David Aprizon; Virdaus, Saivol; Hardinanto, Aris (Institut Agama Islam Negeri Curup, 2024)
This research examines the urgency and challenges of eradicating foreign bribery in Indonesia, utilizing the perspective of Islamic law as an ethical and moral framework. Although Indonesia has committed to the eradication of corruption through ratification of the United Nations Convention against Corruption (UNCAC) and participation in the G20 Anti-Corruption Working Group, the persistence of a stagnant Corruption Perception Index (CPI) score and the absence of specific regulations on foreign bribery indicate a gap between international commitments and domestic implementation. Through a normative legal method, this research analyzes the legal framework and corruption eradication practices in comparison to the principles of fairness, transparency, and accountability in Islamic law. The results show that there are significant gaps in the regulation and practice of combating corruption, especially in relation to combating foreign bribery. This research recommends reforming regulations that not only meet international standards but also accommodate ethical and moral values from Islamic law, as well as emphasizing the importance of international cooperation based on the principle of solidarity in goodness. Efforts to eradicate foreign bribery in Indonesia require a comprehensive approach, combining legal reform, integration of Islamic values, and strengthening international cooperation, to increase the effectiveness of the fight against corruption and strengthen integrity and public trust.